The Use of Numbered Head Together Technique on Students Reading Ability in Narrative Text (An Experimental Studies at the Eleventh Grade Students of SMK N 11 Semarang) - Isna Nur Adhini (Universitas Muhammadiyah Semarang, 2017)
This research aims to find out whether or not numbered heads together technique effective in improving students reading ability in narrative text. The population of the research was the eleventh grade students of SMK N 11 Semarang in the academic year of 2016/2017. As Number Head Together technique consists of four steps: numbering each student, asking questions, head together, and answering questions. The research method was an experimental research, which conducted in two classes; the experimental group (XI Multimedia 1) and control group (XI Multimedia 3) as the sample. The research conducted into six meetings. Before the research did, the instrument had tested at the second grade students of SMK N 11 Semarang. There were 20 questions that used in this research. In the first meeting, the pre-test was given before the teaching and learning activity in those classes. Then, in the second up to fourth meeting, the students in the experimental class were given treatment by using Number Head Together technique and the students in the controlled class were given conventional teaching. Finally, in the sixth meeting, the students in those classes were given post-test. It was used to determine whether there was significant difference between students score in experimental and control group or not. The result of the data was found that the pre-score average in experimental group was 65.52 and control group was 63.38. Based on the results, it could be concluded that Numbered Head Together gave a significant effect on reading skill achievement.